Job satisfactions and dissatisfactions of male teachers in the Division of Quezon City - Cadorna, Constancio Laborte 1929- (s.n.], 1969)
This study identified the satisfaction and dissatisfaction of male teachers employed in the Division of City Schools of Quezon City. Based on the findings, it was recommended that male teachers be given salary adjustments; participation in planning, executing and evaluating; equal work for equal pay; creation of positions for paper work helper; and benefits that other government employees enjoy.